An Exploratory Study of the Diurnal Variation and Reliability of Biomarkers Related to Physiological Damage Experienced in Work-Related Musculoskeletal Disorders. Issue 3 (2nd October 2015) - Christian, Marc; Nussbaum, Maury A.
Abstract: Objectives: Select biomarkers derived from such tissue damage have been proposed as a tool for predicting MSD risk. Factors beyond the exposure to biomechanical stress, although, may influence these biomarkers and thus should be quantified. The purpose of this exploratory study was to determine (1) whether diurnal variations exist for Cartilage Oligomeric Matrix Protein (COMP), Interleukin-6 (IL6), and Creatine Kinase (CK); and (2) if these diurnal variations are influenced by personal factors including age, obesity status, and gender. Methods: Twenty-seven participants were dichotomously classified by age (young = 24.7 [3.9], older = 55.2 [5.0]), body mass index (BMI) (not obese = 23.1 [2.2], obese = 34.1 [2.9]), and gender (males = 14, females = 13), and had blood samples drawn at six time points over a 24-hour period (22:00, 07:00, 10:00, 14:00, 18:00, and 22:00) during which any strenuous physical activity was restricted. Results: COMP levels were significantly higher for males, had significant diurnal variation ( p < 0.01), and this diurnal variation differed between genders ( p = 0.05). IL6 did not have any significant diurnal variation or differences related to age, obesity status, or gender. CK levels exhibited significant diurnal variation ( p = 0.05), and levels were significantly influenced by age ( p < 0.07) and an obesity status × gender interaction ( p < 0.02). Reliability (between two samples at 22:00), measured by the intraclass correlation, was classified as "excellent" for all biomarker levels. Conclusions: Diurnal changes in COMP and CK may reflect differences in body composition between groups. The present results may aid in future study interpretation or design utilizing these biomarkers in the occupational environment.